Feasibility of Hot Melt Extrusion in Converting Water-Based Nanosuspensions into Solid Dosage Forms - Erasmo Ragucci; Marco Uboldi; Adam Sobczuk; Giorgio Facchetti; Alice Melocchi; Mauro Serratoni; Lucia Zema (Pharmaceutics)
Aim: In addition to numerous benefits provided by nanosuspensions (NSs) (e.g., enhanced saturation solubility, increased area for interaction with fluids), they suffer from major stability, handling and compliance issues. To overcome these challenges, we evaluated the feasibility of hot melt extrusion (HME) in transforming a cinnarizine-based NS, selected as a case study, into granules for oral intake. Methods: Thermoplastic polymers, in principle compatible with the thermal behavior of the selected drug and characterized by different interaction mechanisms with aqueous fluids, were used as carriers to absorb the NS and were processed by HME. Results: The extruded granules pointed out good physio-technological characteristics, a drug content > 85% with coefficient of variation (CV) < 5% and tunable in vitro performance coherent with the polymeric carriers they were composed of. Particle size as well as the solid state of cinnarizine was checked using several analytical techniques in combination (e.g., DSC, SEM, FT-IR, Raman). Depending on the composition of the granules, and specifically for formulations processed below 85 °C, the drug was found to remain crystalline and in the desired nanoscale. Conclusions: HME turned out to be a versatile process to transform, in a single-step, NSs into multi-particulate solid products for oral administration showing a variety of release profiles.